Efficacy of Magnesium Supplementation on Glycemic Control in Type 2 Diabetes Patients: A Meta-Analysis - Chua, Francis Bryant; Cinco, Jude Erric; Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2017)
Objectives. To evaluate if magnesium supplementation, in addition to standard therapy, improves fasting blood sugar (FBS) and/or glycosylated hemoglobin (HbA1c) in patients with type 2 diabetes mellitus (T2DM) compared to placebo or other comparator. Methodology. We searched MEDLINE/PubMed, Cochrane Library, Acta Medica Philippina, Health Research and Development Information Network (HERDIN) and references of reviewed journals from 1966 to July 2015 using the following search terms: “magnesium” OR “magnesium supplementation” OR “magnesium replacement”, AND randomized controlled trial AND diabetes OR diabetes mellitus OR non-insulin dependent diabetes mellitus OR diabetic OR diab* (with MeSH, where available). Studies were retrieved and rated independently using the standards provided by The Cochrane Collaboration. High quality trials were included in a systematic review and meta-analysis. Results. Of the 689 records screened, 10 studies were included in the qualitative synthesis and 7 studies in the meta-analysis. Pooled data showed a non-significant trend towards improvement in glycemic control in the magnesium-treated group (mean difference -0.19, CI -0.58 to 0.21). There was a stronger but still non-significant trend in T2DM patients with hypomagnesemia (mean difference -1.16, CI -2.92 to 0.6). Conclusion. Routine magnesium supplementation for improvement in glycemic control in T2DM patients cannot be recommended based on data from included studies in this meta-analysis.